Protocol for non-invasive pulsed-Doppler evaluation of blood flow in the mouse ophthalmic artery - Radwa Awad; Emil Martin; Anilkumar K. Reddy; Iraida Sharina (STAR Protocols)
Summary: The number of reliable and non-invasive techniques to characterize ocular blood flow is limited. Here, we present a protocol for identifying a soft tissue window in the orbital aperture using pulsed-Doppler ultrasonography to offer real-time, non-invasive blood flow velocity monitoring in the mouse ophthalmic artery. We describe steps for preparing a mouse, positioning the ultrasound probe, and acquiring and recording signals. We then detail procedures for analyzing results using a workstation equipped with Doppler flow velocity software.For complete details on the use and execution of this protocol, please refer to Sharina et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.